2011
DOI: 10.1016/s1642-431x(12)60064-3
|View full text |Cite
|
Sign up to set email alerts
|

The staining pattern of human sperm with Diff Quik: relationship with sperm head morphology and a sperm chromatin structure assay (SCSA)

Abstract: SUMMARYThe dark staining of human sperm heads by Diff Quik is significantly correlated with abnormal sperm head morphology (r=0.51, p<0.0001), but is not associated with changes in sperm chromatin detected by a sperm chromatin structure assay (SCSA; r=0.18, p>0.09). Whilst valuable in the assessment of head morphology, it is concluded that Diff Quik staining is not a useful substitute for the SCSA to assess human sperm chromatin. Reproductive Biology 2011 11 1: 55-59.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Sperm Morphology Analysis : Sperm were collected from the outlet and evaluated morphologically using Quick III sperm morphology kit 74. Briefly, sperm were collected at the channel outlet 30 min after loading into the inlet, and smeared on the glass slide.…”
Section: Methodsmentioning
confidence: 99%
“…Sperm Morphology Analysis : Sperm were collected from the outlet and evaluated morphologically using Quick III sperm morphology kit 74. Briefly, sperm were collected at the channel outlet 30 min after loading into the inlet, and smeared on the glass slide.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, Moska et al . () concluded that the dark staining seen with Diff‐Quik is not associated with changes in human sperm chromatin detected by the SCSA. Diff‐Quik staining is therefore not a useful alternative to the SCSA.…”
Section: Discussionmentioning
confidence: 97%
“…DQ presents particular advantages as it is routinely employed in clinics for bacteriological and cellular purposes, it is a rapid, simple and inexpensive procedure, and it can be used for concurrent assessment of sperm morphology (Sousa et al ., ). Therefore, the assessment of both sperm morphology and chromatin on the same slide would be attractive to andrology laboratories (Moska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Briefly, a 5-μl drop of the sperm sample was smeared, air-dried and stained with the kit. More than 100 spermatozoa were observed under the microscope with bright field illumination according to the criteria of morphological normality of sperm head (Moska et al , 2011). In fresh ejaculates from the patients (Table S1), the volume of ejaculate and sperm concentration were 2.0–4.1 ml (average 2.9 ml) and 46.0–218.0 × 10 6 cells/ml (average 128.1 × 10 6 cells/ml), respectively.…”
Section: Methodsmentioning
confidence: 99%